Do TikTok Discounts Livestream Triggers Gen Z Impulse Buying Behavior - Ghea Septia Atika Refasa,; Heriyadi,; Bagus Purmono, Bintoro; Barkah,; Helma Malini, (International Journal of Scientific Research and Management (IJSRM), 2023)
The popularity of live streaming has changed the pattern of interaction between buyers and sellers in the modern business world. For business people, live streaming brings benefits because product information can be disseminated instantly. The high number of social media users in Indonesia has also led to new marketing methods, one of which is live streaming. This quantitative study aims to determine the effect of discounts on Livestream sales on the TikTok application on impulsive purchases of generation Z in Indonesia, which are mediated by positive emotions. This study involved 220 people from various regions in Indonesia who were collected online using a purposive sampling technique with a questionnaire. The data was analysed using Structural Equation Modeling (SEM) using AMOS 24. The results showed that discounts during Livestream selling on the TikTok application had a positive and significant effect on impulse purchases of generation Z in Indonesia. Meanwhile, discounts when selling Livestream on the TikTok application have a positive and significant effect on positive emotions. Positive emotions have an indirect effect between discounts during Livestream selling and impulsive purchases of generation Z in Indonesia. These findings can assist online business players in optimizing marketing in the Livestream selling industry, which is currently booming.